Impact of lung block shape on cardiac dose for total body irradiation. (January 2022) - Glenn, Mallory C.; Wallner, Kent; Luk, Samuel M.H.; Ermoian, Ralph; Tseng, Yolanda D.; Phillips, Mark; Kim, Minsun
Highlights: Partial cardiac shielding in TBI is not commonly reported and varies among clinics. We evaluated the effects of cardiac shielding in TBI using 3D beam modeling in a commercial TPS. Partial cardiac shielding can reduce mean heart dose and reduce LAD dose up to 30%. Abstract: Evaluating cardiac dose during total body irradiation (TBI) is of increasing interest. A three-dimensional beam model for TBI was commissioned and lung shielding was simulated in a treatment planning system with the cardiac silhouette partially blocked and unblocked. When blocked, the median heart dose decreased by 6% (IQR = 6%) and the median cardiac V12Gy decreased by 27% (IQR = 17%). The median left anterior descending artery dose decreased 20% (IQR = 12%) for blocked cases. Because using partial heart shielding may result in considerable changes in dose to cardiac structures, TBI protocols should explicitly consider lung block design parameters and their potential effects.